1990
DOI: 10.1002/ana.410270207
|View full text |Cite
|
Sign up to set email alerts
|

Antimyelin basic protein and antimyelin antibody‐producing cells in multiple sclerosis

Abstract: The B-cell response to myelin and myelin basic protein was studied in patients with multiple sclerosis and in patients with acute aseptic meningoencephalitis by using a nitrocellulose immunospot assay. This method allows detection of single cells producing antibodies. Twenty-seven (79%) of 34 patients with multiple sclerosis had cells producing IgG antibodies against myelin, and 11 (57%) of 19 had cells producing IgG antibodies against myelin basic protein in cerebrospinal fluid (CSF), with mean values of 30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 22 publications
4
48
3
Order By: Relevance
“…In MS, we recently showed elevated numbers of plasma cells producing autoantibodies against myelin antigens in CSF, but not in blood (24). Such a sequestration of the immune response to target may also occur for MBP-reactive T cells in MS since such cells were 70-fold more common among CSF cells than PBL.…”
Section: Discussionmentioning
confidence: 97%
“…In MS, we recently showed elevated numbers of plasma cells producing autoantibodies against myelin antigens in CSF, but not in blood (24). Such a sequestration of the immune response to target may also occur for MBP-reactive T cells in MS since such cells were 70-fold more common among CSF cells than PBL.…”
Section: Discussionmentioning
confidence: 97%
“…CSF antibodies have been reported to react with MOG, 26 MBP, 27 and PLP. 28 In addition, CSF B cells reactive with MBP, 29 MAG, 30 and MOG 31 have been found in patients with MS. However, it has also been reported that CSF antibodies do not react with MOG, MBP, or PLP.…”
Section: Effect Of Methylprednisolone On the Cns Antibody Re-mentioning
confidence: 99%
“…Although these arguments are indirect (6,8,9), they justify the intensive research devoted to the human T cell response against MBP over the past years. A key issue raised by these studies is the heterogeneity of the human T cell response to MBP.…”
Section: Introductionmentioning
confidence: 99%